2017
DOI: 10.1021/acs.joc.7b02623
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Unified Total Synthesis of the Xiamycin and Oridamycin Families of Indolosesquiterpenes

Abstract: A unified synthetic strategy toward the oridamycin and xiamycin families of natural products was designed, aiming to access several natural products from a common synthetic intermediate readily prepared from geranyl acetate. Part of this strategy was successfully realized, culminating in the synthesis of oridamycin A and oridamycin B. Key steps include a Mn(III)-mediated oxidative radical cyclization to construct the trans-decalin ring, and a 6π-electrocyclization/aromatization sequence to produce the 2,3-fuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…This is illustrated by the push in the 2010s to prepare xiamycin, a pentacyclic indolosesquiterpene with selective anti-HIV activity, 79 and oridamycin. [80][81][82][83] In 2015, Li reported the electrocyclization of a sesquiterpene-substituted indole starting material 43 that yielded the core of these natural products 44 (Scheme 12, eqn (1)). 84 The conversion of the triene starting material 43 can be completed either with heating in air or under the action of palladium and benzoquinone.…”
Section: Electrocyclization Of 2-or 3-substituted Indolesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is illustrated by the push in the 2010s to prepare xiamycin, a pentacyclic indolosesquiterpene with selective anti-HIV activity, 79 and oridamycin. [80][81][82][83] In 2015, Li reported the electrocyclization of a sesquiterpene-substituted indole starting material 43 that yielded the core of these natural products 44 (Scheme 12, eqn (1)). 84 The conversion of the triene starting material 43 can be completed either with heating in air or under the action of palladium and benzoquinone.…”
Section: Electrocyclization Of 2-or 3-substituted Indolesmentioning
confidence: 99%
“…In the same year, Trotta used a similar thermally initiated electrocyclization strategy to these xiamycin and ori-damycin that differed by the generation of the triene in situ. 85,86 In a later contribution, Sarpong broke with convention by using a 2-substituted indole 45. 87 This change required a photochemical isomerisation of the starting material to yield the desired product.…”
Section: Electrocyclization Of 2-or 3-substituted Indolesmentioning
confidence: 99%
“…Trotta utilized oxime-directed C(sp 3 )-H acetoxylation in the synthesis of bioactive indolosesquiterpene Oridamycin B. [45,46] The key acetoxylation step was accomplished using 10 mol. % of palladium diacetate and 2 equiv.…”
Section: Acyloxylation Of Oximesmentioning
confidence: 99%
“…Trotta reported attempts to employ photoredox catalysts as polyene cyclization initiators during his studies on the total synthesis of xiamycin A (193). 55 While earlier work on (±)-oridamycin A (188) showed that manganese(III)-mediated cyclization gave the trans-decalin 187 with the methoxy ester in the axial position (Scheme 43); photoredox catalysts were able to convert an α-bromo-βketo ester 216 into the same trans-decalin compound 187.…”
Section: Scheme 42 Synthesis Of (±)-Hongoquercin Amentioning
confidence: 99%